Comportamiento epizootiológico de parásitos gastrointestinales en caninos domésticos (canis familiaris) en el bario Zumbalica - Arcos Quispe, María Cristina (2018)
The objective of this research is to register reliable data of gastrointestinal parasites in domestic canines (Canis familiaris) in the Zumbalica neighborhood. A coproparasitic laboratory tests was developed with the method of Sheather to determine the prevalence of parasite load in each sample. Fecal samples were taken from 150 domestic canines. Furthermore, those samples were analyzed in the laboratory, which were determined by variables of sex, race and age of the canine. The analyzes showed the prevalence of gastrointestinal parasites in domestic canines (Canis familiaris) in the Zumbalica neighborhood. 57 cases were positive with a percentage of 38%, and 93 cases were negative with a percentage of 62%. The values gathered in relation to positive cases to gastrointestinal parasites a percentage of 21.92% with Ancylostoma, 3.22% Coccidia, 4,51% Toxocara canis. 9,68% Uncynaria y 0,64% Trichuris. According to the ages, the parasitic load was 0-12 months 8%, 1-5 years with 19.33% and canines older than 5 years with 10%. Gastrointestinal parasites were found in races: German shepherd 2%, Franch poodle 1,33%. Golden retriver 0,67. In contrast, mix-race were more vulnerable to parasites with a percentage of 34 %. Regardless of their size, gastrointestinal parasites can cause serious illness and sometimes even the death of canines.